2021
DOI: 10.1088/1742-6596/2094/2/022077
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental study of the effect of wollastonite on the physical and mechanical properties of concrete

Abstract: As part of the work, an experimental and theoretical study of the effect of adding wollastonite on the physical and mechanical characteristics of concrete was carried out. The internal stress was calculated according to Hooke’s law. The change in the specific volume was determined from the change in the volume of the hydrated phase. The calculation of the chemical interaction was carried out within the framework of thermodynamic equilibrium. According to the results of the work, it was shown that the addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Reference [13] reported the effects of using ground wollastonite based on the conduction of strength and cement hydration tests. Other studies also reported in 2021 using a numerical simulation conducted by [14] evaluated the influence of wollastonite when binding calcium hydroxide. The results showed that the addition of wollastonite led to the reduction of the specified volume because of the CH binding phase.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [13] reported the effects of using ground wollastonite based on the conduction of strength and cement hydration tests. Other studies also reported in 2021 using a numerical simulation conducted by [14] evaluated the influence of wollastonite when binding calcium hydroxide. The results showed that the addition of wollastonite led to the reduction of the specified volume because of the CH binding phase.…”
Section: Introductionmentioning
confidence: 99%